Dedikasi Gereja Terhadap Realisasi Misi Dalam Menunaikan Amanat Agung - Haposan Simanjuntak; Moralman Gulo; Viktor Deni Siregar; Tetty Mardiana Manalu; Mika Manalu (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
Church dedication in carrying out God's mission is an obligation that must be carried out because it is the main task and responsibility of church institutions to remain faithful and consistently realize it. The purpose of writing this article is to provide a theoretical contribution through ideas or ideas about how the church's dedication in realizing the mission Allah in the world with the right efforts to maximize the completion of the mandate as a whole. The method used in this paper is the literature review method by collecting data in the form of observations, analysis of books, articles, magazines, websites and other sources related to the topic of discussion and looking at the links from each library source used, and all sources used are described. based on the provisions of the research. The result of this discussion is that the church is able to complete the great commission in the world in the right way, then the church is able to produce quality missionaries with various upbringings that are applied and the church consistently carries out its missions with various predetermined actions